Situation Report: Bulgaria, 22 March 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Encho Staykov Speech at CC Plenum Yugov's Flight to Guinea: Telegram to Tito: Stop in Tunis Commentary on Argentina Lukanov's Interview with "Gazetta del Popolo" Recognition of Algeria Bulgarian Komsomol CC Plenum Trade Union Congress Bulgarian Delegation to International Women's Meeting